Inclusive Education in India: a Paradigm Shift in Roles, Responsibilities and Competencies of Regular School Teachers - Das, Ajay Kumar; Sharma, Sushama; Singh, Vinay Kumar (JOURNAL OF INDIAN EDUCATION, 2012)
The success of inclusive education programmes depends on a number of variables. One of such variables, and perhaps the most important one, is the regular classroom teacher. The nature of their work has undergone a tremendous change since the implementation of inclusive education programmes in India. They are now required to perform a number of additional tasks in order to meet the needs of diverse learners. This paper first discusses the change in their roles and responsibilities in the context of inclusive education. It then provides a review of literature on additional competencies that they would need to have in order to be successful in inclusive classrooms. A brief application of this information for programme planners and administrators is also discussed.